Zastosowanie metod optymalizacyjnych w systemach logistyki agrobiznesu - Drelichowski, Ludosław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
In the paper were presented circumstances decided about a dynamic development of new methods of logistics management in companies. Introduction of new logistic solutions was realised simultaneously with updating new specific standard software supporting dissemination of modern organisational concepts. In the work were described also optimisation models used in packages as procedures of making of operational decisions, what is unique standard applied in management information systems.